Biotrophic Plant-Microbe Interactions - Pietro D. Spanu (Frontiers Research Topics, 2017)
Throughout their life, plants interact with all sorts of microbes. Some of these are detrimental and cause disease; some interactions are mutually beneficial for both partners. It is clear that most, if not all, of the interactions are regulated by highly complex checks and balances sustained by signalling and exchange of messengers and nutrients. The interactions where both partners are alive for a significant part of their time together are called biotrophic. In this e-book we bring together 33 articles representing the current state-of-the-art in research about diverse biotrophic plant-microbe associations aimed at describing and understanding how these complex and ubiquitous partnerships work and ultimately support much of the land-based biosphere.